Effects of saddle height on economy in cycling - Peveler, W. W. (The Journal of Strength and Conditioning Research, 2008)
Research has demonstrated that properly adjusting saddle height is important for both performance and injury prevention during cycling. Peer-reviewed literature recommends the use of a 25° to 35° knee angle for injury prevention and 109% of inseam for optimal performance. Previous research has established that these 2 methods do not produce similar saddle heights. Previous research has also compared anaerobic power among a 25° knee angle, a 35° knee angle, and 109% of inseam and found an increase in anaerobic power at a 25° knee angle. While anaerobic power production has been compared between these 2 methods, aerobic power and economy have not been. The purpose of this study was to determine the difference in economy between these 2 methods of adjusting saddle height. Fifteen subjects, consisting of 5 cyclists (all men) and 10 noncyclists (2 men and 8 women), participated in this study. A graded exercise protocol was utilized in order to determine intensity for the remaining trials. On the last 3 trials, subjects rode for 15 minutes at the resistance at which they reached 70% of VO2max on a cycle ergometer. VO2, heart rate (HR), and rating of perceived exertion (RPE) were compared to detect differences in economy between saddle heights. No significant differences were noted in HR or RPE. VO2 was found to be significantly lower at a saddle height set with a 25° knee angle when compared to a 35° knee angle and 109% of inseam. Findings from this study support the use of a 25° knee angle for both performance and injury prevention.